Financial Crime in Socialist Poland and Its Causes in the Light of Polish Central Statistical Office (GUS) Statistics - Błażejczyk-Majka, Lucyna; Macyra, Roman (Studia Historiae Oeconomicae, 2016)
It might seem natural to think that the socialist model of the economy, and a reality where collective property prevailed, eliminated the problem of financial crime. But did it really? This paper, which presents the scale of this type of crime as reflected by GUS (Polish Central Statistical Office) statistics, is an attempt at answering this question. At the same time we would like to present the “3 Cs” model (circumstances, character, chance), in which all the “C” factors occurred simultaneously, but on each occasion each of these had a different impact on the particular criminal act.